P193 Glycopyrronium once daily provides rapid and sustained bronchodilation and is well tolerated in patients with COPD: the SHINE study. (19th November 2012) - Bateman, E; Hashimoto, S; Gallagher, N; Green, Y; Horton, R; Henley, M; Banerji, D
Abstract : Introduction: NVA237 (glycopyrronium bromide) is a once-daily inhaled long-acting muscarinic antagonist for the treatment of COPD. The SHINE study evaluated the efficacy and safety of QVA149, a fixed-dose combination of indacaterol and glycopyrronium, compared with indacaterol, glycopyrronium, open-label tiotropium and placebo in patients with COPD. Methods: This 26 week, multicentre, double-blind, parallel-group, placebo and active controlled (open-label tiotropium) study randomised male or female patients ≥40 years of age with moderate-to-severe COPD (post-bronchodilator FEV1/FVC <0.7 and FEV1 ≥30% to <80% predicted) and smoking history ≥10 pack-years to receive once-daily QVA149 (110/50µg), indacaterol (150µg), glycopyrronium (50µg refers to the quantity of the glycopyrronium moiety present in the capsule, which corresponds to a delivered dose of 44 µg), placebo (all delivered via the Breezhaler® device) and tiotropium (18µg; delivered via the Handihaler® device) (2:2:2:1:2). The primary efficacy endpoint was trough FEV1 (mean of 23h 15min and 23h 45min post-dose) at Week 26. Here we report the results of the efficacy and safety of glycopyrronium versus tiotropium and placebo. Results: Of the 1192 patients randomised (glycopyrronium [n=475]; tiotropium [n=483]; placebo [n=234]); 88.3% completed the study with the mean age in glycopyrronium, tiotropium and placebo groups being 64.3, 63.5 and 64.4 years, respectively. At Week 26, glycopyrronium was superior to placebo for mean trough FEV1 (treatment difference: 120mL; p<0.001). A similar significant improvement was observed with tiotropium versus placebo (treatment difference: 130mL; p<0.001). Significant improvement was also seen with glycopyrronium compared with placebo in other outcome measures evaluating lung function (table ). Serial spirometry in a subset of patients (glycopyrronium [n=63]; tiotropium [n=70] and placebo [n=31]) showed statistically significant improvements in FEV1 with glycopyrronium and tiotropium versus placebo at all assessed time-points on Week 26. The incidence of adverse events was similar between groups (61.3% glycopyrronium; 57.3% tiotropium and 57.8% placebo). Conclusion: Glycopyrronium 50µg once daily provided rapid and sustained bronchodilation over 26 weeks and was well tolerated. The onset of action of glycopyrronium was faster than tiotropium on Day 1 and the FEV1 AUC 0–12h, 12–24h and 0–24h profiles at Week 26 were similar, thereby showing good 24-hour efficacy. Prof Eric Bateman has served on advisory boards for Boehringer Ingelheim, AstraZeneca, Elevation Pharma, Napp Pharma, Novartis, Almirall, Forest, and Merck and Takeda; has served as a consultant to Navigant Consulting, IMS consulting group, ALK-Abello, Almirall, Hoffman la Roche, and ICON; has been paid lecture fees by AstraZeneca, ALK-Abello, Chiesi, Boehringer Ingelheim, GlaxoSmithKline, Nycomed/Takeda, Novartis, Pfizer, and Indegene Lifesciences Ltd. Prof Shu Hashimoto has no conflicts of interest.